The impact of value engineering on embodied greenhouse gas emissions in the built environment: A hybrid life cycle assessment. (15th January 2020) - Yu, Man; Robati, Mehdi; Oldfield, Philip; Wiedmann, Thomas; Crawford, Robert; Nezhad, Ali Akbar; Carmichael, David
Abstract: While traditional value engineering (VE) is primarily driven by cost saving, this study aims to comprehensively and reliably investigating the impact of traditional VE on the embodied greenhouse gas (GHG) emissions in the Australian built environment. An Australian-specific hybrid life cycle assessment (LCA) is developed and applied to a mixed-use building complex located in central Sydney, Australia. A list of GHG emissions intensities (GEIs) for 118 construction products is derived from hybrid LCA, demonstrating an average increase of 20% than the corresponding process-based GEIs. By applying the hybrid GEIs, the assessment of the case study building proves that traditional VE can potentially provide environmental benefits through the dematerialisation of the building. These benefits are small in this instance, with a capital cost reduction of 0.72% equating to an embodied GHG reduction of 0.32%, or a total of −267 t CO2 e (i.e. -3 kg CO2 e/m 2 gross floor area), but if such savings were rolled out across the entirety of new building stock in Australia, the accumulated GHG emissions reduction would be significant. Concrete, reinforcing steel and timber formwork are the hotspots for cost and embodied GHG emissions reduction. Manufacturing and electricity are the originating industries that jointly contribute to more than 80% of the embodied GHG emissions. Highlights: Hybrid GHG emissions intensities (GEIs) of 118 construction products are generated. Process-based GEIs are 20% lower than their corresponding hybrid GEIs. Value engineering can reduce embodied emissions through dematerialisation. Concrete, steel and timber are the hotspots for cost and emissions reduction. Manufacturing and electricity jointly contribute to more than 80% of the emissions.